PEMBUKTIAN VISUM ET REPERTUM PADA TINDAK PIDANA PENGANIAYAAN YANG MENGAKIBATKAN KEMATIAN - Indah Wulandari; Arsyad Aldyan (Sebelas Maret University, 2023)
This article analyzes theproofof Visum et Repertum onthe criminal act of persecution resulting in death. The purpose of this article is to find out Visum et Repertum from the perspective of evidentiary law onthe criminal act of persecution resulting in deathin the context ofacase study ofDecisionNumber 80/Pid.B/2022/PN Krg. This research is normative or doctrinal legal research that is prescriptive and applied. This research uses a case approach with the types of primary legal materials and secondary legal materials. The technique of collecting legal materials using document studies or literature studies. This research uses legal material analysis techniques with a deduction syllogism method. Based on this study, the results were obtained that Visum et Repertum has met the perspective of evidentiarylaw, especially in the criminal act of persecutionresultingin death in the context of a case study of Decision Number 80/Pid.B/2022/PN Krg. From the perspective of evidentiary law, Visum et Repertum is included in the category of evidence and can have the power of proof as documentary evidence, expert testimony, and directive evidence.Keywords: Death; Persecution; Proof; Visum et Repertum